L’ impact de la Croissance Économique sur la Pauvreté et L’inégalité Dynamiques en Afrique: effets de réciprocité - NAQAR, Ilyass; El BAKOUCHI, Mounir (Revue Internationale des Sciences de Gestion, 2021)
The relationship between economic growth and poverty is a topic of crucial interest. It has therefore become essential to know whether, in fact, growth in developing countries is helping to reduce poverty and inequality, or if it is amplifying it. This paper proceeds to test empirically the relationship between growth, poverty and inequality. An empirical analysis of the economic growth impact on poverty and inequality as well as that of poverty on economic growth and inequality. Our analysis was done on a non-cylindrical panel of 28 African countries. The main variables were the absolute poverty rate at $1.25, GDP per capita and the Gini index. To these variables we added the net official development assistance received per capita, the population growth rate and indicators of good governance (corruption, Government effectiveness, and political stability).